Open surgical management of pediatric urolithiasis: A developing country perspective - Syed A Rizvi; Sajid Sultan; Hussain Ijaz; Zafar N Mirza; Bashir Ahmed; Sherjeel Saulat; Sadaf Aba Umar; Syed A Naqvi (Indian Journal of Urology, 2010)
Objectives : To describe decision factors and outcome of open surgical procedures in the management of children with stone. Materials and Methods : Between January 2004 and December 2008, 3969 surgical procedures were performed in 3053 children with stone disease. Procedures employed included minimally invasive techniques shockwave lithotripsy (SWL), percutaneous nephrolithotomy (PCNL), ureterorenoscopy (URS), perurethral cystolithotripsy (PUCL), percutaneous cystolithotripsy (PCCL), and open surgery. From sociomedical records demographics, clinical history, operative procedures, complications, and outcome were recorded for all patients. Results : Of 3969 surgeries, 2794 (70%) were minimally invasive surgery (MIS) techniques to include SWL 19%, PCNL 16%, URS 18.9%, and PUCL+PCCL 16% and 1175 (30%) were open surgeries. The main factors necessitating open surgery were large stone burden 37%, anatomical abnormalities 16%, stones with renal failure 34%, gross hydronephrosis with thin cortex 58%, urinary tract infection (UTI) 25%, and failed MIS 18%. Nearly 50% of the surgeries were necessitated by economic constraints and long distance from center where one-time treatment was preferred by the patient. Stone-free rates by open surgeries were pyelolithotomy 91%, ureterolithotomy 100%, and cystolithotomy 100% with complication rate of upto 3%. Conclusions : In developing countries, large stone burden, neglected stones with renal failure, paucity of urological facilities, residence of poor patients away from tertiary centers necessitate open surgical procedures as the therapy of choice in about 1/3rd of the patients. Open surgery provides comparable success rates to MIS although the burden and nature of disease is more complex. The scope of open surgery will remain much wide for a large population for considered time in developing countries.